CpG and UpA dinucleotides in both coding and non-coding regions of echovirus 7 inhibit replication initiation post-entry. - Fros, JJ; Dietrich, I; Alshaikhahmed, K; Passchier, TC; Evans, DJ; Simmonds, P (eLife Sciences, 2017)
Most vertebrate and plant RNA and small DNA viruses suppress genomic CpG and UpA dinucleotide frequencies, apparently mimicking host mRNA composition. Artificially increasing CpG/UpA dinucleotides attenuates viruses through an entirely unknown mechanism. Using the echovirus 7 (E7) model in several cell types, we show that the restriction in E7 replication in mutants with increased CpG/UpA dinucleotides occurred immediately after viral entry, with incoming virions failing to form replication complexes. Sequences of CpG/UpA-high virus stocks showed no evidence of increased mutational errors that would render them replication defective, these viral RNAs were not differentially sequestered in cytoplasmic stress granules nor did they induce a systemic antiviral state. Importantly, restriction was not mediated through effects on translation efficiency since replicons with high CpG/UpA sequences inserted into a non-coding region were similarly replication defective. Host-cells thus possess intrinsic defence pathways that prevent replication of viruses with increased CpG/UpA frequencies independently of codon usage.